Efektivitas Pelayanan Kartu Identitas Anak Melalui Program Kalimasada Di Kelurahan Rungkut Kidul Kota Surabaya - Andini Salsabilla; Yusuf Hariyoko (Jurnal Relasi Publik, 2024)
Public services are a series of activities carried out to meet the community's needs for goods, services and administrative services in accordance with statutory regulations. Population administration, as part of public services, has an important role in the survival of society. Law Number 23 of 2006 concerning Population Administration emphasizes the importance of population administration services, which include processing population documents such as Kartu Identitas Anak (KIA), Kartu Tanda Penduduk (KTP), and Kartu Keluarga (KK). In the city of Surabaya, population administration is carried out through the Population and Civil Registration Service and sub-district offices, for example in Rungkut Kidul Sub-District there are problems such as a lack of awareness among residents of the importance of complete population data. The Kalimasada program innovation is the government's effort to overcome this problem. Thus, through the Kalimasada program innovation, it is hoped that the people of Rungkut Kidul Village will become more aware of the importance of population administration and maintaining the orderliness of their population documents.